2018
DOI: 10.3892/mmr.2018.8838
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of a congenital split‑hand/split‑foot malformation 4 pedigree

Abstract: In the present study whole-exome sequencing using the Complete Genomics platform was employed to scan a proband from a split-hand/split-foot malformation (SHFM) 4 family. The missense mutation c.728G>A (p.Arg243Gln) in the TP63 gene was revealed to be associated with SHFM. Sanger sequencing confirmed the sequences of the proband and his father. The father was diagnosed with SHFM and harbored a CGG-to-CAG mutation in exon 5, which produced a R243Q substitution in the zinc binding site and dimerization site of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The c.728G>A p.(Arg243Gln) variant has been already reported as pathogenic in several EEC3 patients in the literature. 7 , 8 , 9 , 10 Moreover, similar pathogenic variants were reported at the same amino acid position (c.727C>T p.(Arg243Trp); c.728G>T p.(Arg243Leu)). 7 , 11 , 12 , 13 Arg243 is localized in the DNA binding domain of the TP63 protein, a domain where missense mutations are often described in EEC3 syndrome.…”
Section: Discussionsupporting
confidence: 59%
“…The c.728G>A p.(Arg243Gln) variant has been already reported as pathogenic in several EEC3 patients in the literature. 7 , 8 , 9 , 10 Moreover, similar pathogenic variants were reported at the same amino acid position (c.727C>T p.(Arg243Trp); c.728G>T p.(Arg243Leu)). 7 , 11 , 12 , 13 Arg243 is localized in the DNA binding domain of the TP63 protein, a domain where missense mutations are often described in EEC3 syndrome.…”
Section: Discussionsupporting
confidence: 59%
“…SHFM is characterized as split‐hand/foot malformation (Yang, Lin, Zhu, Luo, & Lin, ) (Table ). There are 12 different SHFM‐related TP63 mutations (approximately 9.3% of TP63 mutations), including missense and nonsense mutations (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutchinick O. M et al reported R97C in the DNA-binding domain of TP63 in Mexican patients with isolated SHFM (Zenteno et al, 2005). Lin G et al reported that c.728G>A (p.Arg243Gln) in the TP63 gene was associated with SHFM (Yang et al, 2018). There is no report that TP63 translocation causes SHFM.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor of p53 family, TP63 is encoded by TP63 locating on 3q28 and is homologous to TP53 and TP73 and plays an essential role in regulating epithelial, limb, and craniofacial development (Yang et al, 1999). It is described that TP63 acts as one of the most frequently mutant gene which accounts for about 10% of SHFM (Yang et al, 2018). As of now, 148 TP63 mutations have been identified, including 115 missense/nonsense mutations, five mutations in regulatory sequence, five splicing substitutions, 13 small deletions, five small insertions, one small indels, two gross deletions, and two gross insertions.…”
Section: Introductionmentioning
confidence: 99%